(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Corporate tax strategy plays a critical role in shaping a company’s financial health, risk exposure, and overall shareholder value. In India, businesses adopt various tax strategies to optimize their liabilities while complying with regulatory requirements. The impact of these strategies on shareholder value depends on factors such as transparency, compliance, and risk management. This study explores the relationship between corporate tax strategies and shareholder value through two Indian case studies: Tata Steel’s transparent tax approach and Vodafone’s high-profile tax dispute. Tata Steel’s commitment to ethical tax practices, compliance with regulations, and proactive engagement with tax authorities has strengthened investor confidence, enhanced its reputation, and contributed to stable stock performance. By mitigating legal risks and ensuring financial predictability, Tata Steel has successfully safeguarded shareholder interests. On the other hand, Vodafone’s tax dispute with Indian authorities over a 2 billion capital gains tax liability exemplifies the risks associated with tax-related litigation. The prolonged legal battle, compounded by the Indian government’s retrospective tax amendment, led to financial uncertainty, legal costs, and reputational damage. This controversy resulted in stock price volatility and diminished shareholder value. The contrasting outcomes of these case studies highlight the significance of a well-structured corporate tax strategy. Companies that prioritize transparency, compliance, and risk management tend to attract long-term investors and sustain market credibility. Conversely, aggressive tax avoidance or disputes can lead to legal penalties, financial instability, and erosion of shareholder trust. In conclusion, corporate tax strategy is a crucial determinant of shareholder value in India. Firms that align their tax policies with ethical governance and regulatory compliance not only avoid legal complexities but also foster sustained investor confidence and financial stability. This study underscores the need for Indian corporations to balance tax efficiency with responsible corporate governance to maximize shareholder value.